Lie, Cheat, and Steal: How Harmful Brands Motivate Consumers to Act Unethically. Issue 2 (6th December 2017) - Rotman, Jeff D.; Khamitov, Mansur; Connors, Scott
Abstract : While brand punishment—through either individual or collective action—has received ample attention by consumer psychologists, absent from this literature is that such punishment can take the form of unethical actions that can occur even when the consumer is not personally harmed. Across three studies, we examine consumers' propensity to act unethically towards a brand that they perceive to be harmful. We document that when consumers come to see brands as harmful—even in the absence of a direct, personal transgression—they can be motivated to seek retribution in the form of unethical intentions and behaviors. That is, consumers are more likely to lie, cheat, or steal to punish a harmful brand. Drawing on these findings, we advance implications for consumer psychologists and marketing practitioners and provide avenues for future research in the area. Abstract : This article is part of the issue "Marketplace Morality"